A review of Multibody Dynamic versus Finite Element Analyses applied in palaeoanthropology: what can we expect for the study of hominin postcranial remains? - Alicia Blasi-Toccacceli; Guillaume Daver; Mathieu Domalain (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
"Multibody Dynamic Analysis" (MDA) and "Finite Element" Analysis (FEA) are commonly used to investigate biomechanical solicitations relative to a movement. These approaches have been also used in palaeontology to bring extinct animals, such as hominins, "back to life". The purpose of this study is to report on the available literature on the use of MDA and FEA in postcranial palaeoanthropology. We briefly introduce the theoretical aspects of modelling and simulation applied to biomechanics. The theoretical basis and fields of application of MDA and FEA are then presented. A synthesis of the literature highlights palaeoanthropological issues, variables derived, findings obtained and methodological limitations to keep in mind. More generally, this study synthesizes a conceptual framework and recommendations for the use of such approaches in form-function relationships in an evolutionary context.